Recommendations for Pain Management in Cancer Patients - Dave, Pallav (Asian Journal of Pharmaceutical Research and Development, 2024)
Pain is a symptom that is reported in cancer patients with the prevalence varying from 33% to 64%. Addressing pain remains a critical aspect of cancer treatment with research showing that pain management in this population remains inadequate. Addressing pain is instrumental because of the impact it has on a patient’s life. It affects clinical outcomes, contributes to poor quality of life, and leads to psychological distress. Barriers remain the key challenge that contributes to inadequate management. Addressing these barriers can lead to better outcomes. Carrying out a comprehensive patient assessment and screening is recommended before beginning pain management. Pain is multidimensional in nature and for many patients, different factors may be contributing to pain. Conducting a comprehensive assessment helps to identify these factors. Comprehensive assessment also helps to capture important information that can contribute to better pain management. After conducting an assessment, pain management should begin. Cancer pain can be managed using pharmacological and non-pharmacological interventions. The interventions should aim to improve patient comfort and function. The interventions should also provide more benefits than adverse effects. One of the mainstay interventions in managing cancer pain is opioids. Opioids should be given in accordance with recommendations from different guidelines to ensure they are effective.